The Afroporteña press and Afro-Argentine’s thought in the late nineteenth century - Yao, Jean-Arsène (Historia y Comunicación Social, 2015)
The journalistic boom that occurred in Argentina from the second half of the nineteenth century saw the emergence of an active afroporteña press that defend the interests of the black community. This paper, in addition to reviewing the history of the Afro-Argentines newspapers, emphasizes the role played by the elite of African descent in the promotion of modernity among his brothers, while exploring the possible bases for an identity in the ideas spread.
Keywords: afroporteños; newspapers; politics; integration; progress